Statistical analysis of COVID-19 in Erbil-Kurdistan/Iraq: Using Parametric Survival Models - Mawlood, Kurdistan I.; Othman , Sarween A. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract—The basic idea of this study focused on using three parametric survival models (Weibull Model, Lognormal Model, Log Logistic Model) instead of nonparametric ones for modeling and estimating affecting factor parameters of Covid-19 patient’s. The data set of this study was obtained from Arzheen private hospital in Erbil city. The results indicated that, the models have not reached to the same variables that have an impact on the Covid-19 patient’s data in Erbil city. Moreover, the results indicated that the Lognormal Model describes the data well or give the best fit for our data of Covid-19 survival patients in Erbil city. Comparison among models were done based on two model selecting criterion; Akaike Information Criterion (AIC) and Bayesian information criterion (BIC). The results obtained by utilizing the statistical packages (Mat-lab V. 14, Stata V. 16 and STATGRAPHICS V. 19).